Contribution of single‐gene defects to congenital cardiac left‐sided lesions in the prenatal setting. (1st August 2020) - Sun, H.; Yi, T.; Hao, X.; Yan, H.; Wang, J.; Li, Q.; Gu, X.; Zhou, X.; Wang, S.; Wang, X.; Wan, P.; Han, L.; et al.
ABSTRACT: Objectives: To explore the contribution of single‐gene defects to the genetic cause of cardiac left‐sided lesions (LSLs), and to evaluate the incremental diagnostic yield of whole‐exome sequencing (WES) for single‐gene defects in fetuses with LSLs without aneuploidy or a pathogenic copy‐number variant (pCNV). Methods: Between 10 April 2015 and 30 October 2018, we recruited 80 pregnant women diagnosed with a LSL who had termination of pregnancy and genetic testing. Eligible LSLs were aortic valve atresia or stenosis, coarctation of the aorta, mitral atresia or stenosis and hypoplastic left heart syndrome (HLHS). CNV sequencing (CNV‐seq) and WES were performed sequentially on specimens from these fetuses and their parents. CNV‐seq was used to identify aneuploidies and pCNVs, while WES was used to identify diagnostic genetic variants in cases without aneuploidy or pCNV. Results: Of 80 pregnancies included in the study, 27 (33.8%) had a genetic diagnosis. CNV‐seq analysis identified six (7.5%) fetuses with aneuploidy and eight (10.0%) with pCNVs. WES analysis of the remaining 66 cases revealed diagnostic genetic variants in 13 (19.7%) cases, indicating that the diagnostic yield of WES for the entire cohort was 16.3% (13/80). KMT2D was the most frequently mutated gene (7/66 (10.6%)) in fetuses with LSL without aneuploidy or pCNVs, followed by NOTCH1 (4/66 (6.1%)). HLHS was the most prevalent cardiac phenotype (4/7) in cases with a KMT2D mutation in this cohort. An additional six (9.1%) cases were found to have potentially deleterious variants in candidate genes. Conclusions: Single‐gene defects contribute substantially to the genetic etiology of fetal LSLs. KMT2D mutations accounted for approximately 10% of LSLs in our fetal cohort. WES has the potential to provide genetic diagnoses in fetuses with LSLs without aneuploidy or pCNVs. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Contribución de los defectos unigénicos a las lesiones cardíacas congénitas del lado izquierdo en el ámbito prenatal Objetivos: Estudiar la contribución de los defectos unigénicos a la causa genética de las lesiones cardíacas del lado izquierdo (LCLI) y evaluar el desempeño del diagnóstico incremental de la secuenciación hologenómica (SHG) para los defectos unigénicos en los fetos con LCLI sin aneuploidía o sin variación patógena en el número de copias (pCNV, por sus siglas en inglés). Métodos: Entre el 10 de abril de 2015 y el 30 de octubre de 2018 se reclutaron 80 mujeres embarazadas diagnosticadas con LCLI, las cuales se sometieron a una interrupción del embarazo y a pruebas genéticas. Las LCLI elegibles eran la atresia o estenosis de la válvula aórtica, la coartación de la aorta, la atresia o estenosis mitral y el síndrome del hemicardio izquierdo hipoplásico (SHIH). La secuenciación CNV (CNV‐seq) y la SHG se realizaron de forma secuencial en muestras de estos fetos y de sus padres. La CNV‐seq se utilizó para identificar las aneuploidías y las pCNV, mientras que la SHG se utilizó para identificar las variantes genéticas de diagnóstico en los casos sin aneuploidías o pCNV. Resultados: De 80 embarazos incluidos en el estudio, 27 (33, 8%) tuvieron un diagnóstico genético. El análisis de la CNV‐seq identificó seis (7, 5%) fetos con aneuploidía y ocho (10, 0%) con pCNV. El análisis de la SHG de los 66 casos restantes manifestó variantes genéticas de diagnóstico en 13 (19, 7%) casos, lo que indica que el comportamiento del diagnóstico del SHG para toda la cohorte fue del 16, 3% (13/80). El KMT2D fue el gen que mutó más frecuentemente (7/66 (10, 6%)) en los fetos con LCLI sin aneuploidía o pCNV, seguido de NOTCH1 (4/66 (6, 1%)). El SHIH fue el fenotipo cardíaco más prevalente (4/7) en los casos con mutación de KMT2D en esta cohorte. En seis casos (9, 1%) adicionales se encontraron variantes potencialmente perjudiciales en los genes con riesgo. Conclusiones: Los defectos unigénicos contribuyen sustancialmente a la etiología genética de las LCLI fetales. Las mutaciones de KMT2D representaron aproximadamente el 10% de las LCLI en esta cohorte fetal. La SHG tiene el potencial de proporcionar diagnósticos genéticos en fetos con LCLI sin aneuploidía o sin pCNV. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd. 摘要: 产前单基因缺陷对先天性心脏左侧病变的促成 目标: 探究单基因缺陷对先天性心脏左侧病变(LSL)遗传病因的促成，并评估全外显子组测序(WES)对LSL胎儿(无异倍体或致病性拷贝数变异)单基因缺陷的递增诊断率。 方法: 在2015年4月10日至2018年10月30日之间，我们招募了80名被诊断患有LSL的孕妇，她们都已终止妊娠并进行了基因检测。符合本研究条件的LSL包括主动脉瓣闭锁或狭窄、主动脉缩窄、二尖瓣闭锁或狭窄和左心发育不全综合征(HLHS)。对来自胎儿及其父母的样本依次进行了CNV测序(CNV‐seq)和WES。CNV‐seq用于识别异倍体和致病性拷贝数变异(pCNVs)，而WES则用于在无异倍体或pCNVs的病例中识别诊断性遗传变异体。 结果: 在本研究的80例受试怀孕中，有27例(33.8%)得到了基因诊断。CNV‐seq分析识别出六个(7.5%)有异倍体的胎儿和八个(10.0%)有pCNVs的胎儿。对剩下的66例采用WES分析，揭示出13个(19.7%)病例中有基因变异，表明WES对所有受试者的诊断率为16.3%(13/80)。KMT2D是LSL胎儿中(无异倍体或pCNVs)最频繁的突变基因(7/66(10.6%))，其次是NOTCH1(4/66(6.1%))。在所有受试者中有KMT2D突变的病例中，HLHS是最常见的心脏表型(4/7)。我们在另外六例(9.1%)中发现了含潜在有害变异的候选基因。 结论: 单基因缺陷极大地促成了胎儿LSL的遗传病因。在我们的所有受试胎儿中，KMT2D变异约占LSL的10%。WES具有为LSL胎儿(无异倍体或pCNVs)提供基因诊断的潜力。版权 © 2019 ISUOG。由威利父子公司(John Wiley & Sons Ltd)出版。